Testing for Asymmetric Employer Learning and Statistical Discrimination - Suqin Ge; Andrea Moro; Beibei Zhu (Global Labor Organization (GLO), 2020)
We test if firms statistically discriminate workers based on race when employer learning is asymmetric. Using data from the NLSY79, we find evidence of asymmetric employer learning. In addition, employers statistically discriminate against non-college educated black workers at time of hiring. We also find that employers directly observe most of the productivity of college graduates at hiring and learn very little over time about these workers.
Keywords: J71; D82; J31; 330; statistical discrimination; employer learning; asymmetric learning